The Role of Leadership Styles in Improving Educational Standards: Teachers' Perspectives - Sari, Nila; Ilham, Dodi; Hasbi, Hasbi; Mardhiah, Mardhiah (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
This study analyzes teachers' perceptions of the principal's leadership style in enhancing teacher performance, infrastructure, curriculum implementation, and the teaching and learning process at SD Celebes Islamic School Belopa, Kabupaten Luwu. The study involved 37 respondents (27 educators and 10 administrative staff) using a quantitative approach with a survey method. Data analysis is conducted descriptively. The findings reveal that the principal's leadership style significantly influences education quality: 1) The authoritarian style contributes the most to teacher performance development (37.5%) by increasing compliance through strict supervision; 2) In infrastructure provision, the authoritarian style is dominant (41.3%), ensuring facility availability through strict oversight, while the democratic style (41.2%) promotes participation and transparency, and the laissez-faire style (17.5%) offers freedom but negatively impacts maintenance; 3) The democratic leadership style has the greatest impact on curriculum implementation (43.9%), enhancing participation and satisfaction, whereas the authoritarian style (28.1%) supports uniformity but limits innovation, and the laissez-faire style (28.0%) allows freedom in teaching methods; 4) In the teaching process, the democratic style is most effective (38.3%), fostering innovation and teacher involvement, while the authoritarian style (34.5%) reinforces standards but restricts creativity, and the laissez-faire style (27.2%) encourages creativity but leads to inconsistency. The study highlights that a combination of leadership styles tailored to each educational aspect can create a conducive learning environment, emphasizing the importance of flexible leadership to meet dynamic educational needs and improve sustainable quality.